Cellular-resolution gene expression profiling in the neonatal marmoset brain reveals dynamic species- and region-specific differences - Kita, Yoshiaki; Nishibe, Hirozumi; Wang, Yan; Hashikawa, Tsutomu; Kikuchi, Satomi S.; U, Mami; Yoshida, Aya C.; Yoshida, Chihiro; Kawase, Takashi; Ishii, Shin; Skibbe, Henrik; Shimogori, Tomomi (Proceedings of the National Academy of Sciences - PNAS, 2021)
Precise spatiotemporal control of gene expression in the developing brain is critical for neural circuit formation, and comprehensive expression mapping in the developing primate brain is crucial to understand brain function in health and disease. Here, we developed an unbiased, automated, large-scale, cellular-resolution in situ hybridization (ISH)–based gene expression profiling system (GePS) and companion analysis to reveal gene expression patterns in the neonatal New World marmoset cortex, thalamus, and striatum that are distinct from those in mice. Gene-ontology analysis of marmoset-specific genes revealed associations with catalytic activity in the visual cortex and neuropsychiatric disorders in the thalamus. Cortically expressed genes with clear area boundaries were used in a three-dimensional cortical surface mapping algorithm to delineate higher-order cortical areas not evident in two-dimensional ISH data. GePS provides a powerful platform to elucidate the molecular mechanisms underlying primate neurobiology and developmental psychiatric and neurological disorders.